Grammatical Errors in the English Writing of Lower- and Higher-Achieving Learners - Iswati, Luluk (CV. Tripe Konsultan, 2025)
For a lot of EFL (English as a Foreign Language) learners, writing is perceived to be the most challenging skill despite the fast development of technology in learning. This study was aimed at revealing types of grammatical errors made by lower- and higher-achieving learners in their writing. This qualitative study analyzed the essay writing of 19 lower-achieving learners and 42 higher-achieving learners from a private university. The writing was assigned in the classroom withough any help of digital tools. The findings revealed that both levels of learners made morphological, syntactic, lexical, and functional errors. No group of learner demonstrated a tendency of producing a certain type of errors, meaning that both lower- and higher-achieving learners made similar errros. The errors were probably caused by the interference of learners’ first langugae (Indonesian), lack of knowledge and practice, and the complex English writing system. The findings of this study imply the need to employ strategies in giving feedback to learners’ writing and to enhance learners’ awareness about morphological, syntactic, lexical, and functional aspects in their writing.